PENERAPAN MODEL PEMBELAJARAN BERDIFERENSIASI TERHADAP PENINGKATAN HASIL BELAJAR SISWA SMAN 3 LUWU - Putri Ramadhani Amir; Bisyri Abdul Karim; Mustamin; Andi Bunyamin; Muh Aidil Sudarmono R (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on the application of differentiated learning models to improvethe learning outcomes of class X.5 students at SMA Negeri 3 Luwu, especially inthe subject of Islamic Religious Education. The main objective of this study is todescribe the application of the model and its impact on student learning outcomes.The method used is Classroom Action Research (CAR) which is carried out in twocycles, each consisting of two meetings. The subjects of the study were 36 classX.5 students. Data were collected through observation, interviews, tests, anddocumentation. Data analysis was carried out by calculating the percentage andaverage value to assess the activity and completeness of student learningoutcomes. The results showed a significant increase in student learning outcomesafter the application of the differentiated learning model. In the pre-cycle, only 10students completed with a percentage of 27.77% and an average value of 47.2(category "Very Poor"). After cycle I, completeness increased to 21 students(58.3%) with an average value of 67.2 (category